Contribution to the knowledge of the subgenus Rhodobaetis Jacob, 2003 (Ephemeroptera: Baetidae: Baetis) from Central Asia. Part 1 - Sroka, Pavel; Godunko, Roman J.; Novikova, Eugenia A.; Kluge, Nikita J. (Zootaxa, 2012)
A new species, Baetis (Rhodobaetis) taldybulaki sp. nov., is described on the basis of larvae and reared adults from Kyr-gyzstan. The differential diagnosis of this species is provided with regard to other representatives of the subgenus Rhodo-baetis Jacob, 2003. The lectotype of Baetis (Rhodobaetis) issyksuvensis Brodsky, 1930 (male imago) is designated,described and illustrated in order to fix the status of this species and clearly differentiate it from B. taldybulaki sp. nov.The holotype of Baetis (Rhodobaetis) heptapotamicus Brodsky, 1930 is redescribed and a new synonymy is established: B. heptapotamicus = B. mycetopis Brodsky, 1930, syn. n.